“I Cannot See”; Inverse Anton’s Syndrome: A Case Study - Obumneme Chinweuba; Peter Knynenburg (BJPsych Open)
Aims: Abnormalities of vision have long been documented in psychosis. One syndrome of interest is Inverse Anton’s syndrome. This is a rare manifestation of visual abnormality where a person describes being blind despite objective evidence against this. In this case report, we discuss a patient who presents with a complaint of blindness despite evidence to the contrary.